Penggunaan Indikator Film Edible dari Antosianin Ubi ungu untuk Monitoring Kesegaran Jamur Tiram Putih - Seftyani, Mita; Pratoko, Dwi Koko; Kuswandi, Bambang (Pustaka Kesehatan, 2023)
Agriculture products as foodstuffs are needed by many people. One of the processed agriculture products that people like is white oyster mushroom. This was followed by requirements for the quality of white oyster mushroom products, so the analytical tool was needed to determine the freshness of white oyster mushrooms easily and practically. This study aimed to develop an edible freshness sensor based on sweet potato anthocyanin (Ipomoea batatas L.) with an edible membrane mixed between chitosan and corn starch. The edible freshness sensor can be applied to determine the freshness level of white oyster mushrooms with various parameters. The evaluation of the freshness of white oyster mushrooms included shrinkage weight test, pH value, texture value, and sensory evaluation. In determining the value of mean green, the color change of an edible freshness sensor was observed visually and measured using the ImageJ program. The results showed that a change in the color of the freshness sensor is dark purple when the white oyster mushroom is fresh, light purple when the white oyster mushroom is still fresh, and green when the white oyster mushroom is no longer fresh. The value of mean green from the edible freshness sensor increase with decreasing the freshness level of white oyster mushroom.